2005
DOI: 10.1111/j.1365-2362.2005.01497.x
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular hyperfiltration in type 1 diabetes mellitus results from primary changes in proximal tubular sodium handling without changes in volume expansion

Abstract: Our data suggest that the primary event in diabetic glomerular hyperfiltration is an increase in proximal tubular sodium reabsorption. They do not support the hypothesis that systemic volume expansion or ANP mediate glomerular hyperfiltration in patients with normoalbuminuric type 1 diabetes. As such, changes in tubular sodium handling most probably influence tubulo-glomerular feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 48 publications
1
56
0
1
Order By: Relevance
“…Studies in patients with type 1 diabetes support the concept that primary increases in proximal tubular sodium resorption lead to glomerular hyperfiltration through decreased tubulo-glomerular feedback at the macula densa [45]. However, diabetes-induced hyperfiltration has been shown to occur in adenosine A1-receptor-deficient mice, which lack the tubulo-glomerular feedback mechanism [46].…”
Section: Mechanisms Of Hyperfiltration In Diabetesmentioning
confidence: 97%
“…Studies in patients with type 1 diabetes support the concept that primary increases in proximal tubular sodium resorption lead to glomerular hyperfiltration through decreased tubulo-glomerular feedback at the macula densa [45]. However, diabetes-induced hyperfiltration has been shown to occur in adenosine A1-receptor-deficient mice, which lack the tubulo-glomerular feedback mechanism [46].…”
Section: Mechanisms Of Hyperfiltration In Diabetesmentioning
confidence: 97%
“…46 Therefore, the contribution of PGE 2 /EP receptors to changes in salt and water transporters in the PT is of great interest. Our work indicates that PGE 2 increases sodium transporter expression in PT cells via EP 1 -and EP 4 -dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for a primary hyperreabsorption upstream of the macula densa and a potential role in glomerular hyperfiltration was also obtained in diabetic patients, including studies that showed that fractional proximal reabsorption was elevated and positively correlated with GFR (20,54,162). Increasing the cortical interstitial concentrations of adenosine, which is a mediator of TGF (140), normalizes GFR in STZdiabetic rats (154).…”
Section: Primary Tubular Hyperreabsorption Contributes To Glomerular mentioning
confidence: 99%